Trilepisium madagascariense fruit-wastes as cheap feedstock for bioethanol production - Ademakinwa, Adedeji Nelson; Agunbiade, Mayowa Oladele; Agboola, Femi Kayode (Acta Biologica Szegediensis, 2019)
Trilepisium madagascariense fruits are carbohydrate-rich and this study directly fermented the fruit wastes into bioethanol without the need for nutrient supplementation. The total reducing sugar (TRS) present in the mesocarp and seed of T. madagascariense fruit wastes (Tmfw) was fermented to bioethanol using Aureobasidium pullulans. Bioethanol production by A. pullulans was also optimized using Box-Behnken response surface methodology (RSM). The TRS in the mesocarp and seed of Tmfw were 11.2 ± 0.8 and 17.1 ± 1.2 g/L, respectively and further hydrolysis with cellulase resulted in increased TRS indicating the presence of cellulose. Pre-optimization, the bioethanol yield (Yps) and volumetric productivity (Qp) obtained from the fermentation of the seed by A. pullulans were 0.57 ± 0.03 g/g and 0.21 ± 0.02 g/L-1h-1, respectively. The optimum conditions for maximum bioethanol production were pH (5.95), time (24 h) and substrate concentration (5 g/L) resulting in Yps, Qp of 0.66 ± 0.06 g/g and 0.27 + 0.01 g/L-1h-1, respectively after model validation. Tmfw served as a suitable, cheap, non-toxic and readily available substrate especially in Nigeria to produce bioethanol while A. pullulans is a fungus that might be utilized for large-scale industrial bioethanol production.